Our Attempts of Femoropopliteal Bypass - Uysal, Ayhan; Özsin, Kadir Kaan; Tok, Rafet; Yücedağ, Eflatun; Şenol, Sefa; Burma, Oktay; Rahman, Ali (Fırat University, 2007)
Objectives: We aimed to determine the yearly patency of the used grefts and case which is performing of femoro-popliteal bypass because of obstructer artery disease. Materials and Methods: 107 femoro-popliteal bypasses are performed for 89 cases because of the extreme chronic obstructer disease and these bypass operations are evaluated. The disease is diagnosed by the help of physical examination and subtraction angiography. As bypass material; reverse safen ven and polytetrafluoroethylene (PTFE) greft were used. Coroner angiography was performed to case which has got ischemic diversification in its preoperative electrocardiography and angina. The cases are evaluated for a monthly postoperative mortality and morbidity and for yearly primer greft patency. Results: 49 (45.7%) of the 107 bypasses were under knee and 58 (54.3%) of them were upper knee. 81 (75.7%) of the bypasses were achieved by revers safen ven and 26 of them were achieved by PTFE greft. Primer patency was determined as %95.5 at the revers safen ven grefts, and it was determined as 70% at the PTFE grefts. PTCA was performed to the 11 (12.3%) of the cases with coroner artery disease, and to the 15 (16.8%) of them, peripheral vascular attempt was performed after coroner bypass. Conclusion: We suggest that in the cases with the disease of peripheral vascular, safen ven greft must be used because of the high patency rate at the appropriate patients, and because of the coroner artery disease which is commonly associated with the disease of peripheral vascular, the angiography must be performed as a preoperative routine survey. ©2007, Fırat Üniversity, Medical Faculty

Giriş: Tıkayıcı arter hastalığı nedeniyle femoro-popliteal bypass uyguladığımız olguları ve kullanılan greftlerin 1 yıllık patensi oranlarını belirlemeyi amaçladık. Gereç ve Yöntem: Alt ekstremite kronik tıkayıcı arter hastalığı nedeniyle 89 olguya uygulanan toplam 107 femoro-popliteal bypass operasyonu değerlendirildi. Tanı fizik muayene ve dijital substraksiyon anjiyografi ile konuldu. Bypass materyali olarak revers safen ven ve politetrafloroetilen (PTFE) greft kullanıldı. Preoperatif elektrokardiyografisinde iskemik değişiklikler olan ve/veya anjinası olan olgulara koroner anjiografi yapıldı. Olgular ilk 1 aylık postoperatif mortalite ve morbidite ile 1 yıllık primer greft patensisi açısından değerlendirildiler. Bulgular: Yapılan 107 femoro-popliteal bypassın 49'u (%45.7) dizüstü, 58'i (%54.3) ise diz altı idi. Bypasslardan 81'i (%75.7) revers safen ven, 26'sı (%24.3) PTFE greft ile gerçeklestirildi. Primer patensi revers safen ven greftlerde % 95.5 iken PTFE greftlerde %70 olarak bulundu. Koroner arter hastalığı saptanan olguların 11'ine (%12.3) PTCA, 15'ine (%16.8) ise koroner bypass sonrası periferik vasküler girişim uygulandı. Sonuç: Periferik vasküler hastalığı bulunan olgularda yüksek patensi oranları nedeniyle uygun hastalarda öncelikli olarak safen ven greftinin kullanılmasını ayrıca koroner arter hastalığı birlikteliği sık olarak görüldüğünden koroner anjiografinin preoperatif rutin tetkik olarak yapılmasını önermekteyiz. ©2007, Fırat Üniversitesi, Tıp Fakültesi
Femoro-Popliteal By-Pass Girişimlerimiz